2015
DOI: 10.1016/j.apunts.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of chronological age and sexual maturity with skeletal maturity by magnetic resonance imaging of the distal radial epiphysis in adolescent football players

Abstract: Introduction: Although the grade of fusion of the left distal radial epiphysis (LDRE) observed by magnetic resonance imaging (MRI) has been linked to chronological age (CA), its relationship to Tanner stage of the genitals in the Latin American population is unknown. Objective: To evaluate the relationship of CA and sexual maturity with skeletal maturity (SM) determined by MRI of the LDRE in adolescent football players from Medellin, Colombia. Materials and methods: Cross-sectional study that included 60 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, different studies on clavicular development indicated that staging was less reproducible than at other anatomical sites [35,48,83]. Furthermore, for all anatomical sites except the ankle, at least one study reported considerably lower values than 0.80 [19,35,40,41,48,61,79]. No relation between those lower values and MR-sequence or staging technique seemed apparent.…”
Section: Reproducibility Of Stagingmentioning
confidence: 93%
See 2 more Smart Citations
“…However, different studies on clavicular development indicated that staging was less reproducible than at other anatomical sites [35,48,83]. Furthermore, for all anatomical sites except the ankle, at least one study reported considerably lower values than 0.80 [19,35,40,41,48,61,79]. No relation between those lower values and MR-sequence or staging technique seemed apparent.…”
Section: Reproducibility Of Stagingmentioning
confidence: 93%
“…Statistics were extracted from boxplots for the following references: [2,69,70,79]. Moreover, the following authors provided additional data: Markus Auf der Mauer [43,46], Jannick De Tobel [42,[47][48][49], Astrid Junge [44], and Martin Urschler [19,45].…”
Section: Age Distributions In Relation To Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study showed that young Italian male soccer players presented a high inter-individual variability of pubertal stage within the same class of chronological age 20 . This can explain in part by the variability of the physical parameters (TBF, BF%, LBM) in this population 22 . Although exercise training could improve the lipid profile, not difference was found in present study.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, in competitive sports in many European countries, there is currently no legal basis for using X-ray examinations to estimate the ages of healthy youth players (Timme et al, 2017). In this context, several studies mention that, in addition to the X-ray method as the gold standard, an image of the handwrist can also be reliably produced by radiation-free magnetic resonance imaging (Dvorak et al, 2007;Dvorak, 2009;George et al, 2012;Bolívar et al, 2015;Urschler et al, 2016;MRI). Going further, there is also evidence that MRI that does not use ionizing radiation is fundamentally more accurate than X-rays due to its high contrast resolution (Serinelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%